EVALUATION OF THE APPLICATION OF SMK3 IN PCI GIRDER ERECTION WORK USING A CRAWLER CRANE: (Case Study: Construction of Probolinggo - Banyuwangi Toll Road Package 1 Sta -3+881 - Sta 09+00 At Bridge Sta -3+256 Span 40.8 Meters) - Prasetyo, Djoko; Oetomo, Wateno; Sajiyo , Sajiyo (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
The Occupational Safety and Health Management System (SMK3) is a comprehensive framework that is used to regulate various activities and manage occupational safety and health (K3) in a systematic manner. In the context of the Probolinggo Banyuwangi Toll Road Development Project Package 1, the implementation of SMK3 was assessed to determine the level of implementation, identify factors that influenced the implementation, and propose corrective actions. The assessment was conducted based on 166 criteria that were outlined in PP No. 50 of 2012, which is a regulation that governs occupational safety and health in Indonesia. Out of these 166 criteria, it was found that 149 criteria were fulfilled, accounting for a compliance rate of 89.76%. However, there were 17 criteria that were not met, resulting in a non-compliance rate of 10.24%. These non-compliant criteria were categorized as minor issues.Overall, the implementation level of SMK3 in the Probolinggo Banyuwangi Toll Road Development Project Package 1 was deemed satisfactory, as the majority of the criteria were fulfilled. The project also demonstrated adherence to relevant laws and regulations, further confirming its commitment to occupational safety and health. Based on the assessment findings, corrective actions can be proposed to address the non-compliant criteria and improve the implementation of SMK3. These actions may include providing additional training and resources, enhancing communication and coordination among stakeholders, and implementing stricter monitoring and evaluation mechanisms.